Strategi Pembelajaran Holistik Berbasis Religious Quotient (RQ) pada Pendidikan Anak Usia Dini: Kajian Teoretis dan Studi Kasus - Afnan (Kartika: Jurnal Studi Keislaman, 2026)
This article examines holistic learning strategies based on Religious Quotient (RQ) as an effort to integrate cognitive, affective, and spiritual aspects in early childhood education. The research employs a descriptive qualitative approach utilizing literature study, document observation, content analysis, and a case study at "TK Negeri Pembina 1 Bangko" early childhood classroom. The findings reveal that RQ-based learning strategies combining spiritual and reflective activities, integration of ruhiological values in classroom practices, and strategic use of media and technology effectively foster students' spiritual awareness, enhance self-reflection, and strengthen spiritual values in daily life. The case study demonstrates that the combination of reflective activities, integration of spiritual values, and use of media-technology produces positive behaviors, empathy, and responsibility among young learners. This study recommends that educators develop learning designs that balance academic, emotional, and spiritual aspects through teacher training, consistent implementation, and periodic evaluation so that the goals of holistic education can be achieved sustainably and effectively within the educational system